CONTRIBUTION DE L’ARTISANAT DANS LA DYNAMIQUE DU DEVELOPPEMENT DE LA VILLE D’ISIRO : CAS DE LA MENUISERIE DE 2012 A 2017 (Etude menée à ISIRO, Province du Haut-Uélé, République Démocratique du Congo) - Jean-Luc BANAMBEANISO OPANA,; Trésor HAKIBA KAHINDO, (IJRDO - Journal of Applied Management Science, 2019)
This paper is focused on the contribution of craft industry in the process of development in Isiro. Especially, on carpentry from 2012 up to 2017. We are going to write down a list of craftsmen (artisans). On the contrary, we are going to examine its impact in the process of development of Isiro. This work is based on pointing out the incomes of this self-employed activity an its contibution to the socio-economic life of these artisans.In the end, it is clear that a large number of people work in this field which helps to reduce the rate of unemployment in the town (at least five people for one workshop). Finally, everything seems to indicate that this sector contributes in the process of development in the area because some people get their incomes from it.